Land use change and collaborative manureshed management in New Mexico. Issue 4 (28th September 2021) - Spiegal, Sheri; Williamson, Jebediah C.; Flynn, K. Colton; Buda, Anthony R.; Rotz, C. Alan; Kleinman, Peter J. A.
Abstract: Agricultural communities of New Mexico regularly redistribute manure nutrients from dairies to nearby croplands to fulfill agronomic nutrient needs and protect water quality. Yet competition for water resources can result in land use change that affects these cooperative manure transfers. Focusing on three clusters of New Mexico dairy farms and their surrounding lands (three manuresheds), we calculated the magnitude of land use changes in 2008–2019 and the balance between manure nutrient supply and crop demand in 2019 to assess how past change may predict future prospects for sustainable management. The overall magnitude of change was small, with each manureshed experiencing a different complement: an exchange of cropland and rangeland in the Roosevelt manureshed (7, 975 ha rangeland to cropland; 7, 624 ha cropland to rangeland), a 464‐ha gain in cropland but a 1, 187‐ha loss of "spreadable" land (cropland, rangeland, fallow) to developed land in the Doña Ana manureshed, and relatively minor changes in the Chaves manureshed. Nutrient supply and demand were mainly in balance, but a surplus of manure phosphorus (P) in the Chaves manureshed and a thin margin of P assimilation by croplands in the Roosevelt manureshed point to the need for preserving existing croplands and understanding of effects of dairy manure on shortgrass rangeland. Our assessment suggests that an ideal scenario would entail manure being generated in landscapes with portfolios of productive lands that can sustainably use the manure nutrients to minimize environmental quality concerns and agronomic tradeoffs. Coordinated, participatory, and interdisciplinary research and planning are needed. Core Ideas: Collaborative manureshed management requires agricultural land to utilize manure nutrients. In New Mexico, dairies are clustered in the state's limited cropland base. Losses and gains of cropland, rangeland, and developed land were observed in three manuresheds. Change rates are slow, but development can restrict manureshed management.